The impact of tumor board on cancer care: evidence from an umbrella review - Maria Lucia Specchia; Emanuela Maria Frisicale; Elettra Carini; Andrea Di Pilla; Danila Cappa; Andrea Barbara; Walter Ricciardi; Gianfranco Damiani (BMC, 2020)
Abstract Background Tumor Boards (TBs) are Multidisciplinary Team (MDT) meetings in which different specialists work together closely sharing clinical decisions in cancer care. The composition is variable, depending on the type of tumor discussed. As an organizational tool, MDTs are thought to optimize patient outcomes and to improve care performance. The aim of the study was to perform an umbrella review summarizing the available evidence on the impact of TBs on healthcare outcomes and processes. Methods Pubmed and Web of Science databases were investigated along with a search through citations. The only study design included was systematic review. Only reviews published after 1997 concerning TBs and performed in hospital settings were considered. Two researchers synthetized the studies and assessed their quality through the AMSTAR2 tool. Results Five systematic reviews published between 2008 and 2017 were retrieved. One review was focused on gastrointestinal cancers and included 16 studies; another one was centered on lung cancer and included 16 studies; the remaining three studies considered a wide range of tumors and included 27, 37 and 51 studies each. The main characteristics about format and members and the definition of TBs were collected. The decisions taken during TBs led to changes in diagnosis (probability to receive a more accurate assessment and staging), treatment (usually more appropriate) and survival (not unanimous improvement shown). Other outcomes less highlighted were quality of life, satisfaction and waiting times. Conclusions The study showed that the multidisciplinary approach is the best way to deliver the complex care needed by cancer patients; however, it is a challenge that requires organizational and cultural changes and must be led by competent health managers who can improve teamwork within their organizations. Further studies are needed to reinforce existing literature concerning health outcomes. Evidence on the impact of TBs on clinical practices is still lacking for many aspects of cancer care. Further studies should aim to evaluate the impact on survival rates, quality of life and patient satisfaction. Regular studies should be carried out and new process indicators should be defined to assess the impact and the performance of TBs more consistently.